2006
DOI: 10.1634/stemcells.2005-0403
|View full text |Cite
|
Sign up to set email alerts
|

Accumulated Chromosomal Instability in Murine Bone Marrow Mesenchymal Stem Cells Leads to Malignant Transformation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
378
5
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 530 publications
(419 citation statements)
references
References 31 publications
23
378
5
7
Order By: Relevance
“…The spontaneous transformation was accompanied by loss of INK4a gene expression, MYC alteration and high telomerase activity. Similar findings were reported by Miura et al using murine bone marrow-derived mesenchymal stem cells, which resulted in spontaneous fibrosarcoma formation 94 . The transformation process was also associated with chromosomal abnormalities involving MYC and upregulation of telomerase activity.…”
Section: Telomerase Activity and Telomere Length Regulate Cancer Stemsupporting
confidence: 88%
See 2 more Smart Citations
“…The spontaneous transformation was accompanied by loss of INK4a gene expression, MYC alteration and high telomerase activity. Similar findings were reported by Miura et al using murine bone marrow-derived mesenchymal stem cells, which resulted in spontaneous fibrosarcoma formation 94 . The transformation process was also associated with chromosomal abnormalities involving MYC and upregulation of telomerase activity.…”
Section: Telomerase Activity and Telomere Length Regulate Cancer Stemsupporting
confidence: 88%
“…The potential spontaneous transformation of somatic stem cells should deserve further attention because of their potential clinical use in tissue regenerative medicine. In light of these previous reports, increased telomerase activity may be responsible, at least in part, for the malignant transformation of human and murine mesenchymal stem cells [91][92][93][94] . This finding is not totally unexpected, as alterations in telomere length and telomerase activity may facilitate cancer development by regulating genomic stability and cell lifespan 95 .…”
Section: Telomerase Activity and Telomere Length Regulate Cancer Stemmentioning
confidence: 78%
See 1 more Smart Citation
“…Compared to murine MSC, human MSC in long-term culture greatly differ in their behavior. Two recent reports demonstrated that human bone marrowderived MSC are not bound to undergo transformation when propagated in long-term culture (Miura et al, 2006;Zhou et al, 2006), and under the same culture conditions, human MSC do not exhibit obvious chromosomal abnormalities at late passages (Bernardo et al, 2007b . The cells employed in these cultures were however not obtained from healthy individuals but isolated from subcutaneous fat during operation of complicated appendicitis and it is thus likely that they are not comparable to normal MSC Kassem et al, 2005).…”
Section: Msc and Transformation Riskmentioning
confidence: 99%
“…During long-term culture, murine MSC accumulate chromosomal aberrations and exhibit a malignant transformation phenotype (Zhou et al, 2006). The resulting MSC, when implanted into immunecompromised mice using hydroxyapatite/tricalcium phosphate as a carrier, as well as when injected into the tail vein led to sarcoma formation (Miura et al, 2006). Murine MSC also rapidly acquire chromosomal abnormalities in culture, and after infusion, these cells invaded lung parenchyma and formed tumor nodules with the characteristics of differentiated osteosarcomas (Aguilar et al, 2007).…”
Section: Msc and Transformation Riskmentioning
confidence: 99%